Welcome Address to the Conference Participants - Roman V. Jashenko (Пернатые хищники и их охрана)
On behalf of the Institute of Zoology of the Republic of Kazakhstan, we are pleased to welcome specialists from more than 29 countries who will take part in the III International Scientific and Practical Conference “Eagles of the Palearctic: Study and Conservation” in Almaty. In Kazakhstan, a thematic conference dedicated not just to birds of prey, but to one group – eagles, is being held for the first time. This is a very important step to create a dialogue platform between specialists in this type of birds.